Wage and Employment Impact of Minimum Wage: Evidence from Lithuania - Jose Garcia-Louzao; Linas Tarasonis (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper evaluates the worker-level effects of a historically large and permanent increase in the minimum wage in Lithuania. Our identification strategy leverages variation in workers' exposure to the new minimum wage, and exploits the fact that there has been no increase in the minimum wage in previous years, to account for heterogeneous labor market prospects of low-wage workers relative to high-wage workers. Using detailed administrative records to track workers before and after the policy change, we show that the minimum wage hike significantly increased the earnings of low-wage workers. This direct effect was amplified by wage spillovers reaching the median of the pre-policy income distribution. Overall, we find no negative effects on the employment prospects of low-wage workers. However, we provide suggestive evidence that young workers, highly exposed municipalities, and tradable sectors may be more negatively affected. In contrast, labor market concentration or the presence of envelope wages appear to be associated with lower job losses. Taken together, our findings imply an employment elasticity with respect to the minimum wage of -0.021, and an own-wage elasticity of -0.033, suggesting that wage gains dominated employment losses.
Keywords: J23; J38; J48; 330; minimum wage; employment; wages